2021
DOI: 10.1371/journal.pone.0251274
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, sociocultural and economic coping strategies of mothers or female caregivers of children with a disability in Belu district, Indonesia

Abstract: Caring for children with a disability can cause a range of psychological and socioeconomic challenges for parents and caregivers, such as anxiety, depression, inability to find affordable and appropriate childcare, loss of income and expenses related to disability specific treatment. As part of a study exploring the impacts of childhood disability on mothers or female caregivers and families, and the copy strategies they used, this paper describes strategies employed by mothers or female caregivers to cope wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…The district has a total population of 204,541 people that are distributed among 12 sub-districts [ 34 ]. The district has a state special school for CWD ( Sekolah Luar Biasa Negeri , also known as SLBN), which provides education for CWD at elementary, junior high school, and senior high school [ 35 , 36 ]. There are also two private rehabilitation centers for CWD, which are called Pusat Rehabilitasi Hidup Baru (New Life Rehabilitation Center) and run by sisters of Franciscan, and Bhakti Luhur, run by the sisters of ALMA (Asosiasi Lembaga Misionaris Awam) Congregation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The district has a total population of 204,541 people that are distributed among 12 sub-districts [ 34 ]. The district has a state special school for CWD ( Sekolah Luar Biasa Negeri , also known as SLBN), which provides education for CWD at elementary, junior high school, and senior high school [ 35 , 36 ]. There are also two private rehabilitation centers for CWD, which are called Pusat Rehabilitasi Hidup Baru (New Life Rehabilitation Center) and run by sisters of Franciscan, and Bhakti Luhur, run by the sisters of ALMA (Asosiasi Lembaga Misionaris Awam) Congregation.…”
Section: Methodsmentioning
confidence: 99%
“…As part of a qualitative study exploring impacts of caring for CWD on mothers or female caregivers and their coping strategies [ 35 , 36 ], this paper describes barriers to the access to healthcare and rehabilitation services for CWD in Belu district, Indonesia. This study was conducted from August to September 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The process of data analysis was both deductive and inductive and followed methods described by Ritchie and Spencer's ve steps framework analysis [45,46]. The ve steps include (i) familiarization by reading each transcript repeatedly, marking ideas and providing comments to the data extracts to search for meaning, pattern and ideas; (ii) identifying a thematic framework by making judgements and writing down key issues and concepts from the participants; (iii) indexing all the data by creating open coding to look for similar or redundant codes and reduce them into smaller number by grouping together to reach a few overarching themes and sub-themes; (iv) creating a chart by arranging thematic framework so that data could be compared within each interview and across all interview; (v) mapping and interpretation data as a whole [45,47]. Data analysis was performed in Indonesian and then the selected quotes for publication were translated into English by authors (GAA, NKF) who speak both languages.…”
Section: Discussionmentioning
confidence: 99%
“…This may prompt them to re-examine whether they are sufficiently effective in their parental role. Additionally, the inability to balance between different obligations can result in feelings of guilt and mourning of the lost opportunities, demotivation for daily activities, low satisfaction and feeling of vitality, a negative self-perception and low self-esteem, as well as depression and reduced quality of life [ 5 , 6 , 7 , 8 ]. Even though most families adapt to the situation over time and find their own routine, it has been confirmed that parental perception of the quality of life depends on the severity of the illness and the extent of disability of the child [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%